Identifying and Evaluating Indicators of Gentrification: A Systematic Literature Review - Cabactulan, Mary Jane; Salapa, Aristeo (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study investigates the indicators of gentrification and their applicability across urban, rural, and forestland settings through a systematic literature review guided by the PRISMA framework. Anchored in socio-spatial transformation perspectives, the study synthesizes existing literature to identify recurring patterns and measures of gentrification. A comprehensive search of academic databases and search engines yielded 154 studies, of which 33 relevant publications were selected based on defined inclusion criteria. Data were analyzed through thematic synthesis to determine the most common indicators and their contextual relevance. Findings reveal eleven key indicators of gentrification, with rising housing costs, displacement and marginalization, and demographic changes emerging as the most dominant across settings. Additional indicators include land-use change, shifts in racial or ethnic composition, social and cultural transformation, economic restructuring, and rural landscape changes. These indicators are interconnected and collectively reflect the socio-economic and environmental impacts of gentrification. The study concludes that gentrification is a multidimensional process extending beyond urban areas and recommends context-specific, equitable development frameworks, sustainable land governance, and protection of indigenous and long-standing communities to mitigate adverse impacts. The study aligns with SDG 11 (Sustainable Cities and Communities) and SDG 15 (Life on Land) by addressing inclusive development and sustainable land use. It contributes to socio-economic and environmental sustainability by informing policy, promoting equitable resource management, and supporting community resilience in transforming landscapes.